1982
DOI: 10.1038/bjc.1982.187
|View full text |Cite
|
Sign up to set email alerts
|

Ability of CEA blood levels to reflect tumour burden: a study in a human xenograft model

Abstract: The relationship of serum carcinoembryonic antigen (CEA) levels to tumour size and antigen content was studied in artificially immune-deprived mice bearing human colonic, breast and lung tumour xenografts. Size was measured as in vivo volume and tumour weight at post-mortem. A multiple implant technique combined with early harvest was used to minimize centrilobular tumour necrosis. CEA was extracted from resected tumours with perchloric acid. A radioimmunoassay using chemical precipitation was used to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…These findings are consistent with previous studies at least as regards TPA and CEA (Luthgens & Schlegel, 1981;Skryten et al, 1981;Biorklund, 1983;Quayle, 1982) and suggest that TPA is related to tumoral proliferation while CA15-3 and CEA are tumour mass related antigens. In conclusion, data from this study indicate that in the post-operative follow-up of breast cancer patients, TPA is the most useful of the three tumour markers and CA15-3 TPA is the most suitable combination.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with previous studies at least as regards TPA and CEA (Luthgens & Schlegel, 1981;Skryten et al, 1981;Biorklund, 1983;Quayle, 1982) and suggest that TPA is related to tumoral proliferation while CA15-3 and CEA are tumour mass related antigens. In conclusion, data from this study indicate that in the post-operative follow-up of breast cancer patients, TPA is the most useful of the three tumour markers and CA15-3 TPA is the most suitable combination.…”
Section: Discussionsupporting
confidence: 82%
“…These consisted of 4 colorectal (HK1,6,7,9), one breast (S32) and one lung (p246) tumours. Their characteristics, and the techniques of immune-deprivation, grafting and tumour measurement, together with methods for measuring circulation CEA levels have previously been described in the preceding article (Quayle, 1982 The results are illustrated in Fig. 1.…”
Section: Methodsmentioning
confidence: 69%
“…www.nature.com/scientificreports/ Notably, in this regard, the original FIRE-3 study demonstrated that more patients treated with cetuximab experienced an early tumor shrinkage (68%) than those treated with bevacizumab (49%) 18 . Considering that CEA reflects the tumor burden in mCRC 6 , we speculate that an increased CEA response may be a reflection of tumor shrinkage and a greater depth of response (DpR) in patients receiving an anti-EGFR mAb regimen than in those receiving an anti-VEGF mAb treatment. The DpR is a recently proposed efficacy outcome that is defined as the percentage of tumor shrinkage observed at the nadir compared with the baseline 19 , and an increased DpR www.nature.com/scientificreports/ is regarded as a good prognostic marker for survival outcomes [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…In real-world clinical practice, it is important for medical oncologists to define whether the cancer is progressive or not during systemic chemotherapy for optimizing the treatment. Since changes in the CEA level may reflect tumor burden 6 , 7 , several previous studies of CRC have reported a correlation between changes in CEA level and disease response, suggesting that changes in CEA level may be a good surrogate marker for predicting disease response during systemic chemotherapy 8 14 . However, most of those studies had a limited sample size, and most of the included patients were treated with chemotherapy alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation